FAKTOR KOMPETENSI AUDITOR INVESTIGATIF YANG MEMPREDIKSI EFEKTIVITAS AUDIT INVESTIGASI BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNAN PERWAKILAN PROVINSI JAWA BARAT - Jhon Rinendy; Grace Orlyn Sitompul (Program Studi Magister Manajemen Universitas Advent Indonesia, 2021)
This study aimed to examine the predictors of competency of auditor investigative that can be predicted the effectivity of audit investigative on Badan Pengawasan Keuangan dan Pembangunan (BPKP) West Java Province. The survey research design was employed in this study with convenience random sampling technique. The descriptive-correlational design and multiple regression analysis were used to determine the existing relationship among the variables and the predictors as said earlier. The respondents were 30 regular full-time employees who were working on investigative field of Financial Supervisory Agency and Representative Development. The findings revealed that investigative auditors agree that having competence was an important thing that must be possessed by an investigative auditor; and the level of effectiveness of the investigative audit conducted on BPKP representatives of the province of West Java was sometimes effective. It was found again base on the analysis of the correlation coefficient competency of investigative auditor in the role to the level of effectiveness of audit investigation was positive with (r) = 0.676, which means, there was a significant positive relationship between the competence of investigative auditors and the level of effectiveness of the audit investigation of the respondents’ perception. It was found as well that understanding psychology theory factor could be predicted to increase investigative audit effectiveness.